Control System Structure of the 4th Drive Power Installations for Electric Vehicles - Osadchyy V.V.; Nazarova E.S.; Brylistyy V.V. (Problems of the Regional Energetics)
The main global trend in the automotive industry is a significant increase in the share of hybrid and electric vehicles in total production, as well as the expansion of the related infrastructure. One of the main objectives of the development of an electric vehicle was to increase mileage without recharging and to improve the handling and maneuverability, as well as the passengers’ safety and cargo transportation conditions. The increase in mileage can be achieved both by improving the battery, and by improving the energy efficiency of the electric drive. The passenger safety is largely dependent on the vehicle handling. Therefore, an urgent task is to improve the performance and energy efficiency of the electric vehicles using the electric drive. The aim of this work was to justify the use of the 4-drive installation, which allowed us to redistribute the torque between the drive wheels, as a base for a modern electric vehicle. The redistribution of the moment between the drive wheels by means of an automated electric drive improved the controllability and safety of the vehicle by maintaining the torque of the drive wheels at the maximum possible level under the given driving conditions. Namely, they are the vehicle speed, angle of rotation and coefficient of adhesion of the drive wheels to the road surface. Using this method enabled to improve the energy efficiency compared to the mechanical method of the redistribution of the moment by eliminating the braking losses of the wheels, which required a reduction in the moment.